RESEARCH TRENDS ON INFRARED SPECTROSCOPY FOR COCOA QUALITY: A BIBLIOMETRIC STUDY USING VOSVIEWER - Listanti, Riana; Masithoh, Rudiati Evi; Saputro, Arifin Dwi; Amanah, Hanim Zuhrotul; Wati, Andra Tersiana (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2024)
Infrared spectroscopy is a non-invasive analytical method that is particularly effective for evaluating the chemical makeup and physical quality of cocoa beans. It offers rapid results, minimal sample preparation, low operational costs, and is environmentally sustainable. However, only a limited number of studies have explored the use of infrared spectroscopy in cocoa. This study aims to investigate the research focus concerning the application of Infrared Spectroscopy Technology in cocoa commodities. The methodology employed includes a literature review with a bibliometric analysis approach and systematic literature review : identification, screening, eligibility, and inclusion. The data were collected from the Scopus database. The study results indicate an increase in publications related to the application of Infrared Spectroscopy Technology in cocoa commodities from 1988 to 2024, particularly from 2022 to 2023. Most research papers were published in Q1 journals, with Brazil leading in publications followed by other countries.New themes that emerge in research regarding related to infrared spectroscopy in cocoa include chemical structure, physicochemical properties, chemometrics, and thermogravimetric analysis. This research offers important insights into the present state and future prospects of infrared spectroscopy in cocoa analysis, emphasizing its importance in enhancing cocoa quality assessment and production efficiency in the chocolate industry. By exploring previous research, this study seeks to offer a deeper understanding of the role and potential of infrared spectroscopy technology. This paper conducts a bibliographic review of global studies related to technological applications of infrared spectroscopy in cocoa research, aiming to highlight worldwide scientific contributions and identify prevailing research trends in the field.